2021
DOI: 10.1101/2021.06.15.448530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency chasing of individual megadalton ions in an Orbitrap analyzer improves precision of analysis in single molecule mass spectrometry

Abstract: To enhance the performance of charge detection mass spectrometry, we investigated the behavior of macromolecular single ions on their paths towards and within the Orbitrap analyzer. We discovered that ions in mass beyond one megadalton reach a plateau of stability and can be successfully trapped for seconds, travelling a path length of multiple kilometers, thereby enabling precise mass analysis with an effective resolution of greater than 100,000 at m/z 35,000. Through monitoring the frequency of individual io… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Previous publications have shown that the charge uncertainty is most likely due to collisions or dephasing of ions in the Orbitrap from ion−ion repulsion. 11,23 First, we set out to calibrate our Orbitrap mass analyzer for CD-MS data collection. In the Orbitrap, a single ion's image current is directly proportional to its charge, and prior studies have shown that they scale linearly.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous publications have shown that the charge uncertainty is most likely due to collisions or dephasing of ions in the Orbitrap from ion−ion repulsion. 11,23 First, we set out to calibrate our Orbitrap mass analyzer for CD-MS data collection. In the Orbitrap, a single ion's image current is directly proportional to its charge, and prior studies have shown that they scale linearly.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The removal of the charge state uncertainty removed the artifact mass peaks and resulted in a single mass peak for GroEL that matched the conventional native mass spectrum (Figure 1H,C). Even with no charge state uncertainty, the peaks are slightly broader than their conventional native MS counterparts, and we expect that this loss of m/z resolution is due to frequency drifting of ions over the longer transient times used for CD-MS. 23 We then tested UCD on other proteins and protein complexes with known charge states: MSP1D1(−), BSA, and ADH. With UCD deconvolution, we were able to remove the charge uncertainty from the CD-MS spectra and confidently assign single charge states for MSP1D1(−), BSA, and ADH (Figure 2).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, as higher mass ions seem to be more prone to peak splitting, such centroids will be removed more frequently in the signal filtering step, biasing the quantification of filled and empty capsids and furthermore, reducing sensitivity for high mass, low abundant ion species. These artifacts can be mitigated by reducing somewhat the transient recording time from 1024 to 512 ms, as demonstrated previously ( 8 ). The effect of a shortened transient time on the mass histogram is also shown in Supplemental Figure 1C, where we can see little to no difference between the unfiltered and filtered datasets, when recording for 512 ms.…”
Section: Supplementary Textmentioning
confidence: 79%